Development of ecological competence of the person in the conditions of «ecologi-psychological» interactions of the future experts: theoretical aspects and the general empirical researches - A V Gagarin (Peoples' Friendship University of Russia (RUDN University), 2010)
In this article the structure and the maintenance of ecological competence of the future experts as integrated personal formation is considered. The role of «ecology-psychological» interactions of the future experts in its productive development, the maintenance and types of interactions of the future experts is defined. The data of the general empirical researches is cited. Prospects of the further researches on a problem are planned.